(untitled) (Asian-Australasian Journal of Bioscience and Biotechnology, 2016)
Diclofenac sodium, a non-steroidal antiinflammatory agent was selected as a model drug for the study, which is BCS class II drug (low soluble and high permeable). Poor water solubility of any drug is characterized by low dissolution rate and consequently reduced bioavailability. Numerous methods have been followed in literature to improve the dissolution rate of poorly water soluble drugs. The objective of the present study was to improve the water solubility and the dissolution rate of poorly water soluble diclofenac sodium by solid dispersion (SD) technique. Binary SDs of diclofenac sodium were prepared by physical mixing as well as solvent evaporation technique using a highly water soluble polymer Eudragit E-100 in different drug-to-polymer weight ratios (1:1 to 1:5). The effect of the carrier Eudragit E-100 on the solubility and in-vitro dissolution behavior were investigated spectrophotometrically at 273 nm. It was found that only 11.43% was released within 60 minutes from active diclofenac sodium on the other hand the release of diclofenac sodium from the binary SD formulation of solvent evaporation containing Eudragit E-100 in 1:5 ratio (code: S9) showed the best result which was 98.57% within the same period of time. Evaluation of the properties of the prepared SDs formulations were performed by using Fourier Transform Infra Red (FTIR) spectroscopy. The FTIR spectroscopic data showed that though the stability of drug was enhanced due to Eudragit E-100, but there was absence of considerable drug-polymer interactions. So solid dispersion may be an effective technique to enhance dissolution rate of diclofenac sodium. Asian Australas. J. Biosci. Biotechnol. 2016, 1 (2), 353-361